2009
DOI: 10.1007/s11104-009-9982-4
|View full text |Cite
|
Sign up to set email alerts
|

C: N: P stoichiometry and specific growth rate of clover colonized by arbuscular mycorrhizal fungi

Abstract: Ecological stoichiometry has been widely applied in aquatic ecosystems, but has limited implications in terrestrial ecosystems. The pot experiments with Trifolium repens L. were conducted to demonstrate the relations between C: N: P, biological components and growth rate of clover colonized by arbuscular mycorrhizal (AM) fungi. The results showed that for mycorrhizal clover, N, P concentrations increased with increasing growth rate, in support of the Growth Rate Hypothesis (GRH). Mycorrhizal clover had higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 36 publications
4
24
2
Order By: Relevance
“…In contrast, our results did not agree with those reported by Chen et al (2010) and Freitas et al (2006), who showed that mycorrhizal plants increased N content in the shoot.…”
Section: Non-inoculated (Ni) or Inoculated With Glomus Mosseae (Mmos)contrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast, our results did not agree with those reported by Chen et al (2010) and Freitas et al (2006), who showed that mycorrhizal plants increased N content in the shoot.…”
Section: Non-inoculated (Ni) or Inoculated With Glomus Mosseae (Mmos)contrasting
confidence: 99%
“…Ca content was higher in inoculated plants compared to non-inoculated ones. Marschner & Dell (1994) determined that AMF could be responsible for mineral absorption of about 80% of P and 10% of K. Our findings indicated that AMF colonization had a beneficial effect on plant growth and P, Ca and K absorption, in concordance with Chen et al (2010) and Freitas et al (2006).…”
Section: Non-inoculated (Ni) or Inoculated With Glomus Mosseae (Mmos)supporting
confidence: 65%
See 1 more Smart Citation
“…On the other hand, the stoichiometry in the soil environment of required nutrients (i.e. C, N and P) also influence the benefit from arbuscular mycorrhizas (Chen et al 2010;Johnson 2010). In the experiments reported here, the nutrient solution composition influenced the AM colonization rates and AM plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…In several researches, AM can take nutrient from unreached area in the soil. It is caused by the external hyphae of AM is small in size and can take nutrients from micro pores of soil (Chen et al 2010). The information of association among plant root and AM is still limited, and recently the suitable AM inoculants to seedling of coffee Arabica, the more information of the association among AM and coffee plant is important to study this relationship.…”
Section: Introductionmentioning
confidence: 99%